In Vivo Evaluation of Operative Torque Generated by Two Nickel-Titanium Rotary Instruments during Root Canal Preparation - Gambarini, Gianluca; Galli, Massimo; Seracchiani, Marco; Di Nardo, Dario; Versiani, Marco A.; Piasecki, Lucila; Testarelli, Luca (European Journal of Dentistry, 2019)
Objectives This in vivo study evaluated the operative torque and preparation time of ProTaper NEXT (Dentsply Maillefer; Ballaigues, Switzerland) and EdgeFile X7 (EdgeEndo; Albuquerque, New Mexico, United States) rotary systems during root canal preparation of maxillary premolars.Materials and Methods Ten double-rooted maxillary premolars with independent canals were selected. Each canal in each tooth was prepared with one of the rotary systems (n = 10), ProTaper NEXT or EdgeFile X7. The instruments were rotated at 300 rpm with maximum torque set at 2 N.cm using an electric motor (KaVo; Biberach, Germany) that automatically recorded torque values at every 1/10th of a second (ds).Statistical Analysis Operative torque (N.cm) and preparation time (s) of the first shaping instrument (size 17/.04) of both rotary systems were recorded and statistically compared using the Mann–Whiney U test with a significance level set at 5%.Results No instrument exhibited flute deformation or underwent intracanal failure. No differences were found between the instruments regarding the maximum (peak) torque values (p > 0.05). EdgeFile X7 17/.04 required significantly less preparation time (3.75 seconds interquartile range [IQR]: 3.2–9.0) than ProTaper NEXT X1 (15.45 seconds IQR: 8.35–21.1) (p < 0.05). The median operative torque values of ProTaper NEXT X1 (0.26 N.cm; IQR: 0.18–0.49) were significantly higher compared with EdgeFile X7 17/.04 (0.09 N.cm; IQR: 0.05–0.17) (p < 0.05).Conclusions Although no difference was found between the median peak torque values of ProTaper NEXT X1 and EdgeFile X7 17/.04 instruments, the operative torque and instrumentation time results were impacted by their different designs and alloys during clinical preparation of root canals.
Keywords: EdgeFile; nickel-titanium; ProTaper NEXT; rotary instruments; torque